Outcome of Transplantation Using Organs From Donors Infected or Colonized With Carbapenem‐Resistant Gram‐Negative Bacteria. Issue 10 (15th May 2015) - Mularoni, A.; Bertani, A.; Vizzini, G.; Gona, F.; Campanella, M.; Spada, M.; Gruttadauria, S.; Vitulo, P.; Conaldi, P.; Luca, A.; Gridelli, B.; Grossi, P.
Abstract : Donor‐derived infections due to multidrug‐resistant bacteria are a growing problem in solid organ transplantation, and optimal management options are not clear. In a 2‐year period, 30/214 (14%) recipients received an organ from 18/170 (10.5%) deceased donors with infection or colonization caused by a carbapenem‐resistant gram‐negative bacteria that was unknown at the time of transplantation. Among them, 14/30 recipients (47%) received a transplant from a donor with bacteremia or with infection/colonization of the transplanted organ and were considered at high risk of donor‐derived infection transmission. The remaining 16/30 (53%) recipients received an organ from a nonbacteremic donor with colonization of a nontransplanted organ and were considered at low risk of infection transmission. Proven transmission occurred in 4 of the 14 high‐risk recipients because donor infection was either not recognized, underestimated, or not communicated. These recipients received late, short or inappropriate posttransplant antibiotic therapy. Transmission did not occur in high‐risk recipients who received appropriate and prompt antibiotic therapy for at least 7 days. The safe use of organs from donors with multidrug‐resistant bacteria requires intra‐ and inter‐institutional communication to allow appropriate management and prompt treatment of recipients in order to avoid transmission of infection. Abstract : The authors review donor‐derived transmission events related to carbapenem‐resistant gram‐negative bacterial infection in a highly endemic region, and suggest strategies to minimize this emerging threat in the vulnerable population of solid organ transplant recipients.